The organizational agility: A strategic approach into the promoting process of job engagement for employee's - MEDAREGNAROU, Amar (The International tax journal, 2025)
The current research aims to introduce talents management as a new concept in the field of human resources management, the concept of organizational agility with its three dimensions (sensing agility, decision making agility, practice agility) and the concept of job involvement with its dimensions (cognitive, emotional, and physical). Also to answer the main question which is: How does talents management achieve and work as a strategy to increase the organization agility and to develop job involvement among employees? This is through analysis the theoretical framework of the subject. The result of this research is: talents management achieves organizations agility and it increases the involvement behavior in job.